Some properties on the powers of n-ary relational systems - Chaisansuk,N. (University of Novi Sad, 2015)
In the paper, we study the properties of n-ary relational systems with respect to a decomposition of the corresponding index set. It is a common generalization of certain properties of binary and ternary relational systems. For each of the properties, we give sufficient condition under which this property is preserved by powers of relational systems.